Formation of prerequisites for the renovationist schism among the liberal nobility and clergy of Orel guberniya in 1900–1917 - Timofey Balyko (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
Based on the analysis of the periodicals of Orel guberniya of the early 20th century, as well as information on the public utterances of provincial public fi gures on the Church question in the pre-revolutionary period, the author reconstructs the process of formation of Renovationist schism among the liberal nobility and clergy of the province of Orel, trying to explain the presence of succession between the supporters of the reform of the Church in diff erent periods. The author also traces the emergence of ideas of Christian socialism in the province, which later became central to Soviet Renovationism. The study of the genesis of these ideas in the province during the period from the First Russian revolution to the February revolution makes it possible to understand the connection between religious and political factors in this dramatic period. When describing the events known to historians of the “Church revolution” of 1917 in Orel guberniya, the article draws on a unique material of personal origin, i.e. a detailed description of these events by one of the priests who was a participant and witness. The author of the article formulates his view on the processes of using the ideas of reforming the Church by various political parties from the Cadets to the Bolsheviks, finds a point of convergence of interests of those who fought for political power, and those who, being a certain stratum of the regional clergy, expressed their readiness to ensure the interests of the existing power, quickly changing their “patrons” if necessary. Moreover, attention is drawn to the facts of a rapid and radical change in the political position of certain representatives of Orel priesthood precisely during the implementation of serious revolutionary changes in the Russian state. The author was able to identify these names, specify them in the article and establish the diff erences between the schismatic element and those who really cared about the welfare of the Church.